The preventive effects of natural adjuvants, G2 and G2F on tracheal responsiveness and serum IL-4 and IFN-? (th1/th2 balance) in sensitized guinea pigs (Clinics, 2014)
OBJECTIVE: The effects of natural adjuvants on lung inflammation and tracheal responsiveness were examined in sensitized guinea pigs. METHODS: The responses of guinea pig tracheal chains and the serum levels of interleukin-4 and interferon-gamma were examined in control pigs and three other groups of guinea pigs: the sensitized group and two other sensitized groups treated with either adjuvant G2 or adjuvant G2F (n = 7 for each group). Sensitization of the animals was achieved by injection and inhalation of ovalbumin. RESULTS: The results showed that sensitized animals had increased tracheal responsiveness and increased serum levels of interleukin-4 and interferon-gamma compared to controls (p